Claiming Back our Chickens: Chicken crisis should not dampen the spirits of our South African Heritage Brands - Stone, Ashleigh (The IIE, 2017)
This small-scale qualitative study looked at the current issue of chicken imports and how they have, with great ease, been able to flood the South African markets and take over from brands that have built trusted relationships and heritage over the many years. This research study particularly focuses on the brand Farmer Brown, which is a chicken production company in South Africa and is considered to be premium and rich with heritage as they had a trusted story and relationship with their target market. The research for this study focused on identifying what strategy Farmer Brown could potentially implement in order to take back their top spot in the South African market. This research study employed a qualitative approach and assessed the views and opinions of two different population groups to find out what exactly Farmer Brown was doing right when they had their top spot in the market to now where hardly anybody knows or sees them. From the research conducted on these two groups. specific themes such as; brand image and identity, and brand equity were identified and explored in relation to the consumers perceptions of Farmer Brown. Consumer behaviour and marketing strategies were also considered. The findings were captured from 15 generation X consumers who were familiar with the Farmer Brown brand, 25 general Millennial parents, 5 random shoppers, and 1 professional that is in this industry. Insights from the findings lead to meaningful recommendations to help Farmer Brown take back their place in the South African market. The findings revealed that Farmer Brown needs to target a new audience which the researcher has suggested to be the Millennial generation. Farmer Brown will need to actively and effectively communicate with this audience and position themselves differently in order to claim back their spot. Findings have also revealed that the Millennial generation want slightly different chicken product variations to what Farmer Brown is currently offering and therefore has been recommended that Farmer Brown take note of this generations wants and needs.
Keywords: Imports; Sourh Market; Branding; Chicken products